PENGARUH PAJAK DAERAH, RETRIBUSI DAERAH, DAN BELANJA DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) PADA LAPORAN KEUANGAN PEMERINTAH WILAYAH SUMUT PERIODE 2022-2024 - Steven Limjaya; Hermawan Sutanto; Latersia Br Gurusinga (JURNAL AKUNTANSI BARELANG, 2026)
This study aims to examine the effect of local taxes, local levies, and local spending on Local Own-Source Revenue (PAD) based on the financial reports of the North Sumatra Provincial Government for the period 2022-2024. Local Own-Source Revenue is one of the main indicators in assessing the level of fiscal independence of regions in the context of regional autonomy and fiscal decentralization. This study uses secondary data sourced from the Budget Realization Report (LRA) published by the Directorate General of Fiscal Balance (DJPK). The analysis method applied is panel data regression using the EViews 13 program, preceded by descriptive statistical analysis, classical assumption testing, and selection of the most appropriate regression model. The results show that, partially, local taxes have a positive and significant effect on Local Own-Source Revenue (PAD), while local levies and local spending hurt Local Own-Source Revenue (PAD). Simultaneously, local taxes, local levies, and local spending have a significant effect on Local Own-Source Revenue (PAD) in North Sumatra Province during the research period. These findings indicate that optimizing local tax revenue and effective and productive local expenditure management play an important role in increasing Local Own-Source Revenue and strengthening regional financial independence.